Islands and Rocks: moving towards certainty on the interpretation of Article 121 of the Law of the Sea Convention? - Rebelo, Xavier (Institute of Marine and Environmental Law, 2017)
The regime of islands, as captured in Article 121 of the United Nations Convention on the Law of the Sea (LOSC) grants a 200 nautical mile exclusive economic zone and continental shelf to all islands apart from "rocks which cannot sustain human habitation or economic life of their own." The provision was undoubtedly drafted in an intentionally ambiguous manner in order to strike a compromise between the contrasting views of States surrounding the regime of islands. Consequently, Article 121 is riddled with textual ambiguities. For example, the text does not further define the word "rock"; nor does the provision explain what it means to "sustain human habitation or economic life". As a result of these ambiguities, many States are of the opinion that Article 121 allocates a 200 nautical mile zone to every piece of land that protrudes above water. This provision is problematic as it potentially allocates vast amounts of ocean space to nations claiming sovereignty over tiny uninhabited islands speckled throughout the oceans, severely limiting the space that remains for the "common heritage of mankind". In addition, the ambiguous wording of Article 121 has resulted in various territorial disputes between nations in relation to both the interpretation and application of the Article. This dissertation seeks primarily to investigate whether the international community is moving towards certainty on the interpretation of Article 121 of the LOSC, with particular reference to the distinction between islands and rocks. In doing so, this dissertation will explore the body of jurisprudence of international courts and tribunals insofar as it relates to Article 121 of the LOSC. This is a fruitful exercise as any clarification in this regard will undoubtedly unify State practice surrounding the application of Article 121. This may have the effect of reducing conflict between States and ensuring that ocean spaces around insular formations are apportioned in an equitable and standardised manner.